Analisis Kode Etik Profesi Hakim Terhadap Putusan Kasus Penganiayaan Oleh Terdakwa George Ronald Tannur (Studi Kasus Putusan MA NO. 454/PID.B/2024/PN.SBY) - Amina, Frahnaz; Najla, Shabrina; Azalea, Shaila; Manurung, Abraham; Fauziyyah, Laila (Media Hukum Indonesia (MHI), 2025)
Indonesia as a country of law has law enforcement officers to ensure that the law runs well, one of which is the judge. In carrying out their duties, judges must be independent, impartial, and adhere to the principles of justice and legal certainty. To ensure that judges carry out their duties in accordance with the mandate of the constitution, a set of rules is formed as a guideline called the code of ethics for judges. However, in its implementation, the application of the judicial code of ethics still faces various problems, one of which is the practice of gratification or bribery which has the potential to interfere with the independence and integrity of the judiciary. The problems raised in this article are about the Code of Ethics and Guidelines for the Conduct of Judges in Indonesia and violations of the application of the Code of Ethics for the Professional Judges in the case of abuse involving the defendant George Ronald Tannur. Using the normative legal research method, this study analyzes laws and court decisions regarding the George Ronald Tannur case. The code of ethics and guidelines for the conduct of judges in the Indonesian judicial system aim to maintain the integrity and public trust in the judicial institution. However, in practice, violations are still found, such as alleged bribery in the George Ronald Tannur case. Therefore, it is necessary to strengthen supervision by the Supreme Court and the Judicial Commission to improve the integrity and professionalism of judges.